Pengaruh Kemudahan Penggunaan, Kualitas Pelayanan, Persepsi Keamanan Terhadap Keputusan Penggunaan Brimo Pada Nasabah Bank BRI Kota Malang - Aviv Patul Kholifah; Nur Hidayati; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to determine the effect of ease of use, service quality, security perceptions on the decision to use BRImo at Bank BRI Malang City. The type of research used is quantitative research, with data collection methods by distributing questionnaires. The population in this study are residents of the city of Malang. The sample calculation in this study used the Malhotra formula which produced 95 respondents. The method of determining the sample is using a non-probability sampling method with a purposive sampling technique. This data analysis technique uses SPSS 22.0. This study has fulfilled the validity and reliability tests. The data analysis used in this study is the classical assumption test, multiple linear regression test, statistical test and the coefficient of determination. The results of this study are the variables of ease of use, service quality, and perceived security and simultaneously or partially influence the decision to use BRImo at Bank BRI Malang City. Keywords: Ease of Use, Quality of Service, Perceived Security